Assessment of Water Quality Using Benthic Macroinvertebrate Along Sumber Maron River, District of Gondanglegi Kulon, East Java-Malang, Indonesia - Tawati, Faiza; Risjani, Yenny; Djati, M Sasmito; Yanuwiadi, Bagyo (The Journal of Experimental Life Science, 2020)
Human activities such as agriculture, swimming, livestock, public washing, and the use of latrines around the river are considered as major causes of damage to the river ecosystem, affecting the growth of Macroinvertebrate, and thus assessing the condition of the river. This study aimed to study the composition of Macroinvertebrate and the quality of water health in Sumber Maron River, in the village of Gondanglegi. This research was conducted from March to April 2018. The method used in this research was the quantitative method using primary data. Research stations were identified by considering land-use in nine regions. The sampling technique of total macroinvertebrates was the kicking technique using the manual mesh with a 500 µm applied to the submerged solid substrates. The data were analyzed using a BMWP Index and interpreted by calculating the Average Scores Per Taxon (ASPT). The result of this research represented that there were 20 taxa of macroinvertebrates, which consisted of It belongs to 8 orders (Trichoptera, Coleoptera, Diptera, Tricladida, Decapoda, Odonata, Ephemeroptera, Plecoptera) and four class (Oligochaeta, Hirudinea, Gastropoda, Crustacea). Generally, the lowest taxa groups found in the station A1 (3 taxa), which were the agriculture and toilet (recreation area). Meanwhile, the highest taxa groups were found in station B3, which was the recreation area, by a total of 14 taxa. Macroinvertebrate with the lowest abundance was Gerridae at station A3, which respectively had the number of 1 ind.5m-2. Macroinvertebrate with the highest abundance was Baetidae at the station B3, which is the recreation area, by the number of 549 ind.5m-2. The result of modified BMWP - ASPT analysis showed a value of 3.3 - 5.75, which indicated that the condition of Sumber Maron River was ranging from bad to excellent category. The bad water condition was found in the agriculture and toilet (recreation area), whereas the excellent water condition was found in the swimming pool (recreation area). Canonical Correspondence Analysis (CCA) revealed that environmental variables were significant for an explanation of the variance in the family. Keywords: BMWP-ASPT, Macroinvertebrate, River.